2020
DOI: 10.2196/preprints.26162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient Perceptions on Data Sharing and Applying Artificial Intelligence to Health Care Data: Cross-sectional Survey (Preprint)

Abstract: BACKGROUND Considerable research is being conducted as to how artificial intelligence (AI) can be effectively applied to health care. However, for the successful implementation of AI, large amounts of health data are required for training and testing algorithms. As such, there is a need to understand the perspectives and viewpoints of patients regarding the use of their health data in AI research. OBJECTIVE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The big majority only knew 'somehow' what it meant or even less, which was in a similar range already shown for the German as well as other populations. 21,62 Much more explicitly, our data point out that an application of AI at the bedside is only acceptable for the vast majority of patients if they can be sure that the AI is under continuous control and more specifically, they expect this control to be taken over by a physician. Several respondents strengthened this point in their free text notes explicitly.…”
Section: Study Populationmentioning
confidence: 90%
See 2 more Smart Citations
“…The big majority only knew 'somehow' what it meant or even less, which was in a similar range already shown for the German as well as other populations. 21,62 Much more explicitly, our data point out that an application of AI at the bedside is only acceptable for the vast majority of patients if they can be sure that the AI is under continuous control and more specifically, they expect this control to be taken over by a physician. Several respondents strengthened this point in their free text notes explicitly.…”
Section: Study Populationmentioning
confidence: 90%
“…The big majority only knew ‘somehow’ what it meant or even less, which was in a similar range already shown for the German as well as other populations. 21,62…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Royal Free NHS Foundation Trust was accused of breaching the UK Data Protection Act 1998 when it provided the data of 1.6 million patients to Google for its DeepMind project without consent [11]. A study conducted in the UK showed that the public is more comfortable sharing their health data with the government sector and university but reserved to share their data with commercial companies [12]. However, if the data is made anonymously, participants are more willing to share their data [13].…”
Section: Data Governancementioning
confidence: 99%
“…There is significant variation in patient perception and knowledge of health data and AI, but generally patients were strongly in favour of developing AI that offer improvements in diagnosis and treatment. 35 Patients did have significant concerns about sharing their data when it may ultimately be sold to external organisations to use for profit. 36 Consent, deidentification, and data governance Dermatologists should obtain informed consent from their patients to use their data for ML purposes.…”
Section: Patient Perspectivesmentioning
confidence: 99%